Flame-retardant epoxy glue and preparation method thereof

By preparing a flame-retardant epoxy glue composed of components A and B, using flame retardants such as magnesium hydroxide and vermiculite, functional fillers such as talc powder and chitosan, the problems of high brittleness and insufficient flame retardant performance of epoxy glue are solved, and efficient flame retardant, high temperature resistance and mechanical performance improvement are achieved.

CN119799237AInactive Publication Date: 2025-04-11SHANDONG HIGHDEV NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510063669.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In actual applications, existing epoxy adhesives have problems such as high brittleness, poor impact resistance and mechanical impact resistance, and have not yet met the standards of some industries in terms of fire-proof and flame-retardant performance.

Method used

By using flame retardant epoxy glue prepared in mass ratio of 1.5 to 3:1 by component A and component B, component A includes epoxy resin, flame retardant, functional filler and diluent, and component B includes curing agent and defoaming agent. Magnesium hydroxide and premodified vermiculite are used in the preparation of flame retardants, and are treated with silane coupling agent and a high-energy ball mill to improve compatibility and dispersion. The functional fillers are made of talc, chitosan and alumina.

Benefits of technology

Epoxy adhesives with good flame retardancy, high temperature resistance, high toughness and good comprehensive performance have been achieved, which can meet the flame retardant standards of the aerospace, electronics and electrical industries, and the mechanical properties of the epoxy adhesives are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243614680000121
    Figure BDA0005243614680000121
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly discloses a flame-retardant epoxy adhesive which is prepared from a component A and a component B according to the mass ratio of (1.5-3): 1, the component A is prepared from the following raw materials in parts by weight: 55-85 parts of epoxy resin, 8-15 parts of a flame retardant, 20-35 parts of functional filler, 3-8 parts of a diluent and 0.5-2 parts of a defoaming agent; the component B is prepared from the following raw materials in parts by weight: 45-70 parts of a curing agent and 0.5-2 parts of a defoaming agent. According to the epoxy glue provided by the invention, the flame retardant and the functional filler are synergistically used, so that the indexes such as flame retardance, high temperature resistance, toughness and mechanical properties are very excellent, and the comprehensive performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a flame retardant epoxy adhesive and a preparation method thereof. Background Art

[0002] Epoxy adhesive, also known as epoxy resin adhesive, is an adhesive based on epoxy resin, typically consisting of two components: epoxy resin and a curing agent. Epoxy adhesives based on epoxy resin offer a range of advantages, including strong adhesion, minimal curing shrinkage, excellent corrosion resistance, and superior processability. Therefore, they are widely used for bonding metals, ceramics, plastics, and other materials.

[0003] In actual use, epoxy adhesives suffer from limitations such as high brittleness and poor resistance to impact and mechanical shock. At the same time, with their increasing application, fire resistance has become a necessary performance requirement in many applications. For example, in industries such as aerospace, electronics, and automotive, epoxy adhesive products must meet certain flame retardancy standards to ensure they do not fuel combustion, explode, or cause other dangerous situations in the event of a fire. Furthermore, some civil construction and industrial equipment also require the use of flame-retardant epoxy adhesives to ensure safety.

[0004] There have been many studies on improving the flame retardancy of epoxy adhesives. Generally speaking, the flame retardancy of epoxy adhesives can be improved from the following aspects: (1) Adding flame retardants. Halogen compounds, phosphorus compounds and other flame retardants are added to epoxy resins or curing agents to inhibit combustion reactions; (2) Introducing inorganic fillers. Inorganic flame retardant fillers such as aluminum hydroxide and silicates are added to epoxy adhesives to form a composite flame retardant material; (3) Using flame retardant epoxy resins. Develop epoxy resin raw materials constructed with halogen-free and phosphorus-free structural units; (4) Surface coating treatment. Apply fire retardant paint or coating to the cured surface of epoxy adhesive to form a heat insulation barrier. Around the above aspects, there have been some research reports in the prior art. For example, patent document CN110982465A provides a high-efficiency halogen-free flame retardant epoxy adhesive, including component A and component B. Component A, by mass percentage, includes: 20-50% epoxy resin; 5-10% toughening agent; 10-30% halogen-free flame retardant; 3-5% flame retardant synergist; 3-5% carbonizing agent; 0.1-2% anti-dripping agent; 3-5% diluent. The epoxy adhesive prepared by the above formulation has the following characteristics: flame retardancy, anti-drip, low smoke emission, and excellent bonding performance. However, it can be seen that the epoxy resin only considers the flame retardancy performance, and does not take into account the inherent shortcomings of the epoxy adhesive, such as its brittleness.

[0005] For example, patent document CN109355047A provides a highly flame-retardant and heat-resistant epoxy resin adhesive, the raw materials of which include, by weight: 55-70 parts of epoxy resin, 8-10 parts of brominated lignin, 3-9 parts of polyethersulfone, 5-12 parts of acrylonitrile-styrene-acrylate copolymer, 2-7 parts of polyoxypropyleneamine, 3-8 parts of benzophenone tetracarboxylic dianhydride, 3-9 parts of DMP-30, 2-3 parts of benzyltriphenylphosphonium bromide, 2-5 parts of triglycidyl isocyanurate, 8-11 parts of graphene oxide, 2.5 parts of dodecyl phosphate monoester, and 10 parts of bis(2-3)-bis(2-4)-bis(2-5)-bis(2-6)-bis(2-7)-bis(2-8)-bis(2-9)-bis(2-9)-bis(2-9)-bis(2-3)-bis(2-5)-bis(2-6)-bis(2-7)-bis(2-8)-bis(2-9 ... The adhesive comprises 3.5-3.5 parts of ethylene glycol monomethyl ether, 8-13 parts of ethylene glycol monomethyl ether, 2-3 parts of hexaphenoxycyclotriphosphazene, 2-3.8 parts of silicon carbide, 2-3.7 parts of a silane coupling agent, 2-6 parts of nano-titanium dioxide, and 1-5 parts of carbon nanotubes. The raw materials used are epoxy resin as the primary ingredient, with brominated lignin added to modify the epoxy resin. The phenolic and alcoholic hydroxyl groups in the brominated lignin react with the epoxy resin, introducing the rigid structure of the benzene ring into the system, improving the heat resistance of the resulting adhesive and overcoming the poor heat resistance of epoxy resin alone. Among the above raw materials, the graphene oxide used is expensive, making it unsuitable for large-scale production and application.

[0006] In fact, in addition to flame retardancy, it is very necessary to develop epoxy adhesives with low brittleness (high toughness) and high mechanical properties. In view of this, the present invention is proposed. Summary of the Invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a flame retardant epoxy adhesive and a preparation method thereof, which has good flame retardancy, high temperature resistance, high toughness and excellent comprehensive performance.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a flame retardant epoxy adhesive prepared from component A and component B in a mass ratio of 1.5 to 3:1;

[0010] Component A is prepared from the following raw materials in parts by weight: 55-80 parts of epoxy resin, 8-15 parts of flame retardant, 20-35 parts of functional filler, 3-8 parts of diluent, and 0.5-2 parts of defoaming agent;

[0011] Component B is prepared from the following raw materials in parts by weight: 45 to 70 parts of curing agent and 0.5 to 2 parts of defoaming agent.

[0012] Preferably, the preparation of the flame retardant comprises the following steps:

[0013] Magnesium hydroxide and pre-modified vermiculite are sequentially added into water, stirred, and then a silane coupling agent is added, heated and stirred, and then filtered and dried, and finally ball milled in a high-energy ball mill to obtain a flame retardant.

[0014] Preferably, the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 8-15:0.4-0.85:100:8-12;

[0015] The silane coupling agent is KH550;

[0016] The heating and stirring treatment temperature is 65-85°C and the treatment time is 2-6 hours;

[0017] The ball milling speed is 80-250 rpm, the ball milling medium is zirconium oxide, and the ball milling time is 20-60 min.

[0018] Preferably, the preparation of pre-modified vermiculite comprises the following steps: adding vermiculite to a 1.5-3.5 mol / L sulfuric acid solution, treating at 25-35° C. for 6-12 hours, filtering, washing, and drying to obtain pre-modified vermiculite;

[0019] The usage ratio of vermiculite and sulfuric acid solution is 8-15g:100mL.

[0020] Preferably, the preparation of the functional filler comprises the following steps:

[0021] (1) talc and chitosan are mixed and added to an acetic acid aqueous solution, heated and stirred, and then filtered, washed, and dried to obtain modified talc;

[0022] (2) adding aluminum nitrate to an ethanol solvent, followed by adding ammonium fluoride and ethanolamine, stirring evenly and then heating to react. After the reaction is completed, evaporating the unreacted ethanol solvent, followed by carbonization and calcination, and finally washing and drying to obtain pre-modified alumina;

[0023] (3) adding the pre-modified alumina obtained in step (2) to a solvent containing a strong oxidant for treatment, filtering, washing, and drying the pre-modified alumina to obtain the modified alumina;

[0024] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are sequentially added to water, heated, filtered, washed, dried, ground and sieved to obtain a functional filler.

[0025] Preferably, in step (1), the mass ratio of talc powder, chitosan, and acetic acid aqueous solution is 1:0.6-0.85:10-15 mL; the heating treatment temperature is 60-80° C., and the treatment time is 4-8 h;

[0026] The concentration of the acetic acid aqueous solution is 1 to 2.5 wt%.

[0027] Preferably, in step (2), the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:60-120:0.5-1:7-9.5;

[0028] The heating reaction temperature is 60-80°C and the reaction time is 3-8h;

[0029] The carbonization temperature is 250-255°C, and the carbonization time is 20-45 minutes;

[0030] The calcination temperature is 1020-1040°C, and the calcination time is 1-4 hours.

[0031] Preferably, in step (3), the strong oxidant is selected from a combination of two or three of concentrated sulfuric acid, concentrated nitric acid, and potassium permanganate, and the solvent is ethanol; the ratio of the strong oxidant to the ethanol is 1 g: 4-10 mL; the treatment temperature of the pre-modified alumina in the strong oxidant is room temperature, and the treatment time is 1.5-5 h;

[0032] In step (4), the mass ratio of modified talc powder to modified alumina is 1:0.5-0.85, the heating treatment temperature is 30-40° C., the treatment time is 2-6 h, and the grinding and sieving mesh number is 325-500 mesh.

[0033] Preferably, in component A, the epoxy resin is selected from one or more of E44, E51, and E54;

[0034] The diluent is selected from one or both of butyl glycidyl ether and 1,4-butanediol glycidyl ether; the defoamer is selected from one or more of BYK022 defoamer, BYK037 defoamer, and BYK051 defoamer;

[0035] In component B, the curing agent is selected from one or both of benzylenediamine and m-phenylenediamine; the defoaming agent is selected from one or more of BYK022 defoaming agent, BYK037 defoaming agent, and BYK051 defoaming agent.

[0036] In a second aspect, the present invention provides a method for preparing the flame retardant epoxy adhesive, comprising the following steps:

[0037] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0038] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0039] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The flame retardant epoxy adhesive provided by the present invention has good flame retardancy, good high temperature resistance, high toughness and excellent comprehensive performance.

[0042] (2) The flame retardant epoxy adhesive provided by the present invention is based on epoxy resin, adopts common curing agents and auxiliary agents, and improves the comprehensive performance of epoxy adhesive by using flame retardants and functional fillers. Among them, the flame retardant is mainly made of magnesium hydroxide and vermiculite. The two are relatively common flame retardants. The two are very easy to agglomerate during use, which affects the flame retardant effect. In the present invention, they are subjected to high-energy ball milling treatment in the presence of a silane coupling agent. The use of the silane coupling agent is on the one hand to improve the compatibility between the magnesium hydroxide inorganic particles and the vermiculite and the epoxy resin, and to prevent the re-agglomeration of the magnesium hydroxide and vermiculite after ball milling. On the other hand, the groups introduced by the silane coupling agent can be well combined with the subsequent functional fillers to jointly improve the performance of the epoxy adhesive. In addition, the ball milling treatment can generate certain active sites on the surface of the vermiculite and magnesium hydroxide, which is also conducive to the use of functional fillers. The applicant found in actual research that the use of the above-mentioned ball milling treatment needs to be combined with the use of a silane coupling agent to achieve the best effect.

[0043] (3) The flame retardant epoxy adhesive provided by the present invention is also pre-treated with acid during the use of vermiculite, which is beneficial for removing impurities in the pores and plays a role in preliminary activation.

[0044] (4) The present invention provides a flame retardant epoxy adhesive, wherein the functional filler is mainly composed of talcum powder, chitosan, and alumina, wherein talcum powder can greatly improve the high temperature resistance of epoxy adhesive, reduce the shrinkage rate of epoxy adhesive, and preliminarily improve the mechanical properties of epoxy adhesive; chitosan can play a good bridging role while improving the bonding strength of epoxy adhesive; alumina can play a very good high temperature resistance and wear resistance, and together with talcum powder, improve the mechanical properties of epoxy adhesive. During use, chitosan is first introduced into the present invention to modify talcum powder. The purpose is to improve the compatibility between talcum powder and the subsequent composite alumina and epoxy resin based on the rich functional groups contained in chitosan, and on the other hand, facilitate hydrogen bonding with the amino group contained in the silane coupling agent in the flame retardant to form a large network structure, compact the film formation of epoxy resin, further improve the flame retardancy, high temperature resistance and mechanical properties of epoxy adhesive, and synergistically improve the comprehensive performance of epoxy adhesive. Regarding the use of alumina, the present invention first performs fluorine-doping modification on it, the purpose of which is to improve its dispersibility while facilitating the formation of a hydrogen bond system with other substances. Subsequently, the alumina is treated with a strong oxidant, the purpose of which is to introduce groups such as carboxyl groups, so as to facilitate the efficient formation of composite particles with the hydroxyl groups and the like of chitosan through hydrogen bonds, van der Waals forces, etc., and then synergistically act with the flame retardant.

[0045] In summary, the epoxy adhesive provided by the present invention, through the coordinated use of flame retardants and functional fillers, has excellent flame retardancy, high temperature resistance, low brittleness (high toughness), mechanical properties and other indicators, and has good comprehensive performance. DETAILED DESCRIPTION

[0046] The embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but are not to be construed as limiting the present invention.

[0047] Unless otherwise specified, the chemical reagents and production equipment involved in the present invention were purchased from the market.

[0048] In the present invention, the epoxy resin brand is E51, which is sourced from Baling Petrochemical; the chitosan with a deacetylation degree of about 85% is purchased from Sinopharm Chemical Reagent Co., Ltd.; the talc powder is purchased from Shanghai Shuosi Talc Powder Co., Ltd., with a particle size of about 325 mesh; the vermiculite is purchased from Lingshou County Deyang Mineral Products Processing Plant, with a particle size of about 250 mesh; the concentration of concentrated sulfuric acid is 98%; and the concentration of concentrated sulfuric acid is 68%.

[0049] At the same time, it should be noted that the parts mentioned in the present invention are all parts by weight unless otherwise specified. The processing equipment mentioned, such as the high-energy ball mill, are all mature equipment and are not described in detail in the present invention. It is subject to the implementation of those skilled in the art.

[0050] Example 1

[0051] A flame-retardant epoxy adhesive is prepared from component A and component B in a mass ratio of 2:1; component A is prepared from the following raw materials by weight: 75g of epoxy resin (E51), 10g of flame retardant, 30g of functional filler, 5g of diluent (butyl glycidyl ether), and 1.5g of defoamer (BYK037);

[0052] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0053] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, adding a silane coupling agent KH550 after stirring, heating and stirring (70°C, 4h), filtering, drying, and finally milling in a high-energy ball mill (zirconium oxide, 180rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.65:100:11.

[0054] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 30° C. for 8 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0055] The preparation of the functional filler comprises the following steps:

[0056] (1) Talc and chitosan were mixed and added to a 1.5 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.75:12 mL;

[0057] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (255°C, 25 minutes), calcination (1030°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.7:8;

[0058] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 2 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:8 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0059] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 3h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0060] In this embodiment, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0061] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0062] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0063] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0064] Example 2

[0065] A flame-retardant epoxy adhesive is prepared from component A and component B in a mass ratio of 2:1; component A is prepared from the following raw materials by weight: 75g of epoxy resin (E51), 11g of flame retardant, 31g of functional filler, 5g of diluent (butyl glycidyl ether), and 1.5g of defoamer (BYK037);

[0066] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0067] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, adding a silane coupling agent KH550 after stirring, heating and stirring (75°C, 4h), filtering, drying, and finally milling in a high-energy ball mill (zirconium oxide, 180rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.68:100:10.5.

[0068] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to a 2 mol / L sulfuric acid solution in a ratio of 10 g:100 mL, treating at 30° C. for 10 h, filtering, washing, and drying to obtain pre-modified vermiculite.

[0069] The preparation of the functional filler comprises the following steps:

[0070] (1) Talc and chitosan were mixed and added to a 1.8 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.78:11 mL;

[0071] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (250°C, 25 minutes), calcination (1035°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.72:7.5;

[0072] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 2.5 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:9 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0073] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.68, and after heating (35°C, 4h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0074] In this embodiment, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0075] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0076] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0077] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0078] Example 3

[0079] A flame-retardant epoxy adhesive is prepared from component A and component B in a mass ratio of 2:1; component A is prepared from the following raw materials by weight: 75g of epoxy resin (E51), 10g of flame retardant, 28g of functional filler, 5g of diluent (butyl glycidyl ether), and 1.5g of defoamer (BYK037);

[0080] Component B was prepared from the following raw materials by weight: 48 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0081] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, adding a silane coupling agent KH550 after stirring, heating and stirring (70°C, 5h), filtering, drying, and finally ball milling in a high-energy ball mill (zirconium oxide, 200rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.62:100:9.5.

[0082] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 35° C. for 6 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0083] The preparation of the functional filler comprises the following steps:

[0084] (1) Talc and chitosan were mixed and added to a 2 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.75:9 mL;

[0085] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (60°C, 4h). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (250°C, 25min), calcination (1035°C, 1h), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.65:7;

[0086] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 3 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:9 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0087] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 4h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0088] In this embodiment, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0089] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0090] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0091] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0092] Comparative Example 1

[0093] Compared with Example 1, the flame retardant in Comparative Example 1 was prepared without using KH550, and all other aspects were the same. Specifically, in Comparative Example 1, a flame retardant epoxy adhesive was provided, which was prepared from component A and component B in a mass ratio of 2:1; component A was prepared from the following raw materials by weight: 75g epoxy resin (E51), 10g flame retardant, 30g functional filler, 5g diluent (butyl glycidyl ether), and 1.5g defoamer (BYK037);

[0094] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0095] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, followed by heating and stirring (70°C, 4h), filtering and drying, and finally milling in a high-energy ball mill (zirconium oxide, 180rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite and water is 10:0.65:100.

[0096] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 30° C. for 8 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0097] The preparation of the functional filler comprises the following steps:

[0098] (1) Talc and chitosan were mixed and added to a 1.5 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.75:12 mL;

[0099] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (255°C, 25 minutes), calcination (1030°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.7:8;

[0100] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 2 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:8 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0101] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 3h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0102] In this comparative example, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0103] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0104] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0105] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0106] Comparative Example 2

[0107] Compared with Example 1, the flame retardant in Comparative Example 2 was prepared without high-energy ball milling and was directly mixed. Specifically, Comparative Example 2 provided a flame retardant epoxy adhesive prepared from component A and component B in a mass ratio of 2:1; component A was prepared from the following raw materials by weight: 75 g epoxy resin (E51), 10 g flame retardant, 30 g functional filler, 5 g diluent (butyl glycidyl ether), and 1.5 g defoamer (BYK037);

[0108] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0109] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, stirring, adding silane coupling agent KH550, heating and stirring (70°C, 4h), filtering, and drying to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.65:100:11.

[0110] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 30° C. for 8 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0111] The preparation of the functional filler comprises the following steps:

[0112] (1) Talc and chitosan were mixed and added to a 1.5 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.75:12 mL;

[0113] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (255°C, 25 minutes), calcination (1030°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.7:8;

[0114] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 2 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:8 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0115] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 3h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0116] In this comparative example, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0117] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0118] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0119] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0120] Comparative Example 3

[0121] Compared with Example 1, chitosan is not used in the preparation of the functional filler in Comparative Example 3, and all other aspects are the same. Specifically, Comparative Example 3 provides a flame retardant epoxy adhesive, which is prepared from component A and component B in a mass ratio of 2:1; component A is prepared from the following raw materials by weight: 75g epoxy resin (E51), 10g flame retardant, 30g functional filler, 5g diluent (butyl glycidyl ether), and 1.5g defoamer (BYK037);

[0122] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0123] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, adding a silane coupling agent KH550 after stirring, heating and stirring (70°C, 4h), filtering, drying, and finally milling in a high-energy ball mill (zirconium oxide, 180rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.65:100:11.

[0124] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 30° C. for 8 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0125] The preparation of the functional filler comprises the following steps:

[0126] (1) Adding talc powder to a 1.5 wt% acetic acid aqueous solution, heating and stirring (65°C, 4 h), filtering, washing, and drying to obtain modified talc powder; wherein the mass ratio of talc powder to acetic acid aqueous solution is 1:12 mL;

[0127] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (255°C, 25 minutes), calcination (1030°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.7:8;

[0128] (3) adding the pre-modified alumina obtained in step (2) to ethanol containing a strong oxidant for treatment (room temperature, 2 hours), filtering, washing, and drying after the treatment to obtain modified alumina; wherein the amount ratio of the strong oxidant to the ethanol is 1 g:8 mL; the strong oxidant is obtained by mixing a mixed acid (concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2.5) and potassium permanganate in a volume ratio of 1:1;

[0129] (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 3h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0130] In this comparative example, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0131] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0132] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0133] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0134] Comparative Example 4

[0135] Compared with Example 1, the preparation of the functional filler in Comparative Example 4 does not involve step (3), and the rest are the same. Specifically, Comparative Example 4 provides a flame retardant epoxy adhesive, which is prepared from component A and component B in a mass ratio of 2:1; component A is prepared from the following raw materials by weight: 75g epoxy resin (E51), 10g flame retardant, 30g functional filler, 5g diluent (butyl glycidyl ether), and 1.5g defoaming agent (BYK037);

[0136] Component B was prepared from the following raw materials by weight: 45 g of curing agent (m-phenylenediamine) and 1 g of defoaming agent (BYK037).

[0137] The preparation of the flame retardant includes the following steps: adding magnesium hydroxide and pre-modified vermiculite to water in sequence, adding a silane coupling agent KH550 after stirring, heating and stirring (70°C, 4h), filtering, drying, and finally milling in a high-energy ball mill (zirconium oxide, 180rpm, 30min) to obtain the flame retardant; wherein the mass ratio of magnesium hydroxide, pre-modified vermiculite, water, and silane coupling agent is 10:0.65:100:11.

[0138] The preparation of pre-modified vermiculite includes the following steps: adding vermiculite to 1.8 mol / L sulfuric acid solution in a ratio of 10 g: 100 mL, treating at 30° C. for 8 h, filtering, washing and drying to obtain pre-modified vermiculite.

[0139] The preparation of the functional filler comprises the following steps:

[0140] (1) Talc and chitosan were mixed and added to a 1.5 wt% acetic acid aqueous solution, heated and stirred (65°C, 4 h), filtered, washed, and dried to obtain modified talc; wherein the mass ratio of talc, chitosan, and acetic acid aqueous solution was 1:0.75:12 mL;

[0141] (2) Aluminum nitrate is added to an ethanol solvent, followed by ammonium fluoride and ethanolamine, and the mixture is stirred evenly and then heated to react (65°C, 3.5 hours). After the reaction, the unreacted ethanol solvent is evaporated, followed by carbonization (255°C, 25 minutes), calcination (1030°C, 1 hour), and finally washing and drying to obtain pre-modified alumina; wherein the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:80:0.7:8;

[0142] (3) The modified talc powder obtained in step (1) and the pre-modified alumina obtained in step (2) are added to water in a mass ratio of 1:0.65, and after heating (35°C, 3h), the mixture is filtered, washed, dried, ground and sieved through 325 mesh to obtain a functional filler.

[0143] In this comparative example, a method for preparing the flame retardant epoxy adhesive is also provided, comprising the following steps:

[0144] S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A;

[0145] S2. Mix the curing agent and defoamer in proportion and stir evenly to obtain component B;

[0146] S3. Mix component A and component B in proportion and stir evenly to obtain flame retardant epoxy adhesive.

[0147] The performance test of the sealing materials prepared in Example 1 and Comparative Examples 1 to 4 was carried out as follows:

[0148] Impact strength test is carried out in accordance with GB / T6328-2021;

[0149] The oxygen index test is carried out in accordance with GB / T 2406.3-2022;

[0150] The smoke density test is carried out in accordance with GB / T 8323.2-2008;

[0151] The elongation at break test was carried out according to ASTM D638;

[0152] The tensile strength test was carried out according to ASTM D638;

[0153] The bond strength (tensile shear strength) test is carried out in accordance with GB / T 7124-2008;

[0154] High temperature resistance test: The sample prepared according to GB / T 7124-2008 was placed at 200°C for 5 hours, and then the bonding strength was measured again.

[0155] The test results are shown in Table 1.

[0156] Table 1 Test results

[0157]

[0158] As can be seen from Table 1, the epoxy adhesive prepared by the present invention has good flame retardancy, toughness (high elongation at break) and mechanical properties, and has good application prospects.

[0159] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A flame retardant epoxy adhesive, characterized in that: It is prepared from component A and component B in a mass ratio of 1.5 to 3:1; Component A is prepared from the following raw materials in parts by weight: 55-85 parts of epoxy resin, 8-15 parts of flame retardant, 20-35 parts of functional filler, 3-8 parts of diluent, and 0.5-2 parts of defoamer; Component B is prepared from the following raw materials in parts by weight: 45 to 70 parts of curing agent and 0.5 to 2 parts of defoaming agent.

2. A flame retardant epoxy adhesive according to claim 1, characterized in that: The preparation of flame retardant includes the following steps: Magnesium hydroxide and pre-modified vermiculite are sequentially added into water, and then a silane coupling agent is added after stirring. After heating and stirring, the mixture is filtered and dried, and finally ball-milled in a high-energy ball mill to obtain a flame retardant.

3. A flame retardant epoxy adhesive according to claim 2, characterized in that: The mass ratio of magnesium hydroxide, pre-modified vermiculite, water and silane coupling agent is 8-15:0.4-0.85:100:8-12; The silane coupling agent is KH550; The heating and stirring treatment temperature is 65-85°C and the treatment time is 2-6h; The ball milling rotation speed is 80-250 rpm, the ball milling medium is zirconium oxide, and the ball milling time is 20-60 min.

4. The flame retardant epoxy adhesive according to claim 2, characterized in that: The preparation of pre-modified vermiculite comprises the following steps: adding the vermiculite into a 1.5-3.5 mol / L sulfuric acid solution, treating at 25-35°C for 6-12 hours, filtering, washing and drying to obtain the pre-modified vermiculite; The usage ratio of vermiculite and sulfuric acid solution is 8-15g:100mL.

5. The flame retardant epoxy adhesive according to claim 1, characterized in that: The preparation of functional fillers includes the following steps: (1) mixing talcum powder and chitosan, adding the mixture to an acetic acid aqueous solution, heating and stirring, filtering, washing, and drying to obtain modified talcum powder; (2) adding aluminum nitrate to an ethanol solvent, followed by adding ammonium fluoride and ethanolamine, stirring evenly and then heating to react, evaporating the unreacted ethanol solvent after the reaction, then carbonizing and calcining, and finally washing and drying to obtain pre-modified alumina; (3) adding the pre-modified alumina obtained in step (2) into a solvent containing a strong oxidant for treatment, and filtering, washing, and drying the pre-modified alumina after the treatment to obtain modified alumina; (4) The modified talc powder obtained in step (1) and the modified alumina obtained in step (3) are sequentially added into water, and after heating treatment, the mixture is filtered, washed, dried, ground and sieved to obtain a functional filler.

6. The flame retardant epoxy adhesive according to claim 5, characterized in that: In step (1), the mass ratio of talcum powder, chitosan and acetic acid aqueous solution is 1:0.6-0.85:10-15 mL; the heating treatment temperature is 60-80° C., and the treatment time is 4-8 h; The concentration of the acetic acid aqueous solution is 1 to 2.5 wt %.

7. The flame retardant epoxy adhesive according to claim 5, characterized in that: In step (2), the mass ratio of aluminum nitrate, ethanol solvent, ammonium fluoride and ethanolamine is 10:60-120:0.5-1:7-9.5; The heating reaction temperature is 60-80°C and the reaction time is 3-8h; The carbonization temperature is 250-255°C, and the carbonization time is 20-45 minutes; The calcination temperature is 1020-1040°C, and the calcination time is 1-4 hours.

8. The flame retardant epoxy adhesive according to claim 5, characterized in that: In step (3), the strong oxidant is selected from a combination of two or three of concentrated sulfuric acid, concentrated nitric acid, and potassium permanganate, and the solvent is ethanol; the dosage ratio of the strong oxidant to ethanol is 1 g: 4-10 mL; the treatment temperature of the pre-modified alumina in the strong oxidant is room temperature, and the treatment time is 1.5-5 h; In step (4), the mass ratio of modified talcum powder to modified alumina is 1:0.5-0.85, the heating treatment temperature is 30-40°C, the treatment time is 2-6h, and the grinding and sieving mesh number is 325-500 mesh.

9. The flame retardant epoxy adhesive according to claim 1, characterized in that: In component A, the epoxy resin is selected from one or more of E44, E51, and E54; The diluent is selected from one or both of butyl glycidyl ether and 1,4-butanediol glycidyl ether; the defoamer is selected from one or more of BYK022 defoamer, BYK037 defoamer and BYK051 defoamer; In component B, the curing agent is selected from one or both of benzylenediamine and meta-phenylenediamine; the defoaming agent is selected from one or more of BYK022 defoaming agent, BYK037 defoaming agent and BYK051 defoaming agent.

10. A method for preparing the flame retardant epoxy adhesive according to any one of claims 1 to 9, characterized in that: The steps include: S1. Mix epoxy resin, flame retardant, functional filler and defoamer in proportion and stir evenly, then add diluent and stir evenly again to obtain component A; S2, mixing the curing agent and the defoaming agent in proportion and stirring evenly to obtain component B; S3. Mix the A component material and the B component material in proportion and stir evenly to obtain the flame retardant epoxy adhesive.

Citation Information

Patent Citations

  • Vermiculite-based composite flame retardant and preparation method thereof

    CN104072805A

  • High-temperature-resistant and flame-retardant epoxy adhesive and preparation method thereof

    CN114989756A

  • Flame-retardant boiling-resistant high and low temperature impact-resistant two-component epoxy pouring sealant as well as preparation method and application of flame-retardant boiling-resistant high and low temperature impact-resistant two-component epoxy pouring sealant

    CN115678475A

  • Epoxy resin containing composite flexibilizer and preparation method thereof

    CN118290901A

  • Self-lubricating high-wear-resistance PCR (Polymerase Chain Reaction) polymer composite material as well as preparation method and application thereof

    CN118307946A